2017
DOI: 10.4314/ecajs.v21i3.13
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Burden of Urologic Disease: Admissions Patterns at the Main Teaching Hospital of Ethiopia

Abstract: Background: Sigmoid volvulus (SV) has a considerable geographical variation in its incidence. The purpose of this study was to determine the incidence of SV in Northern Uganda.Methods:A two year retrospective and one year prospective study in 19 hospitals in Northern Uganda from January 2010 to December 2012 was conducted to determine the incidence of sigmoid volvulus. All patients' records with a diagnosis of sigmoid volvulus were included in the study. Ethical approval was obtained from the IRB Gulu Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Many researchers from India, China and Kenya found that stone mostly lye in the upper tract so as in our study [23]. Another study conducted in Nigeria showed contradictory results that 55.7% stones [24] and 75.6% [25] form in the lower urinary tract.…”
Section: Discussionsupporting
confidence: 43%
“…Many researchers from India, China and Kenya found that stone mostly lye in the upper tract so as in our study [23]. Another study conducted in Nigeria showed contradictory results that 55.7% stones [24] and 75.6% [25] form in the lower urinary tract.…”
Section: Discussionsupporting
confidence: 43%
“…5 Studies done locally showed that urolithiasis represent 13.6% to 33.6% of urologic surgical burden which is consistent with our finding, 30.0%. 11,[25][26][27] Furthermore, reports from other countries recognized urolithiasis among the major reasons of urologic surgical admission. 2,3,14 Worldwide, the estimated male to female ratio of urolithiasis ranges from 1.5 to 2.5:1.…”
Section: Discussionmentioning
confidence: 99%
“…It is also the leading diagnosis of elective admission for surgery performed at our University hospital [2]. Esophageal Cancer has an effect of multifaceted severe insult in the physiology and cardiorespiratory reserves of the subjects as it does not only put the patient at significant imbalance due to cachexia as other malignancies do but it also confounds the situation by dysphagia and subsequent dehydration [3]. The presenting symptoms of esophageal cancer usually signify locally advanced disease or distant metastases or both irrespective of histologic type even in developed nations with "early "diagnosis [4,5].…”
Section: Introductionmentioning
confidence: 99%